Fabrication of lead zirconate titanate ceramics for pyroelectric applications - Navarro, A. (Cranfield University, 2001)
The objective of this work was twofold, i.e. to develop an aqueous route for tape casting Lead Ziconate Titanate (PZT)ceramics for pyroelectric applications and to optimise the die-pressing route for reducing defect size and number in bulk Lead Zicronate Titanate ceramics (PZT).